Depolimerisasi Kitosan dari Cangkang Udang dengan Enzim Papain dan Iradiasi Sinar Ultraviolet: Depolymerization of Chitosan from Shrimp Shell Using Papain Enzyme and Ultraviolet Light Irradiation - Rizfi Fariz Pari; Dewi Mayangsari; Safrina Dyah Hardiningtyas (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Chitosan is a natural polymer with positive charge that is good to be applied in the pharmaceutical field as a drug carrier. However, commercial chitosan has a large molecular weight and low degree of deacetylation, so its application is limited due to its low solubility in water. This study aims to determine the effect of the depolymerization method of two classes of chitosan on the market. The types of chitosan used to produce chitooligosaccharide are pharmaceutical grade and food grade. The method used were UV-C light irradiation (75 minutes), papain enzyme hydrolysis (15 g/L for 16 hours, 40oC and pH 5) and a combination of UV and enzymes. The results showed that the grade of chitosan and the depolymerization method affected the characteristics of the product. The three methods used in pharmaceutical grade chitosan produce chitooligosaccharide which dissolved directly in water with a neutral pH. Chitooligosaccharide had yield of >62%, whiteness degree of 99.33%, molecular weight <5.5 KDa, and degree of deacetylation >85%. Food grade chitosan which has been depolymerized by different methods cannot be dissolved in water with a neutral pH. Food grade chitosan through the combination of UV+enzyme depolymerization has the same deacetylation quality as pharmaceutical grade chitosan.